Pengaruh Corporate Governance Dan Pengungkapan Sustainability Report Terhadap Kinerja Keuangan - Agnes Megawaty Lumban Gaol; Suzy Noviyanti (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to determine the effect of corporate governance and the effect of disclosure sustainability report on the financial performance of companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The process of collecting data using a purposive sampling method by obtaining 33 companies for 3 years of observation with 99 observations. The data in this study uses secondary data from annual financial reports and sustainability reports. This research is a quantitative research with data processing using Statistical Product and Service Solution (SPSS). The analysis process used is descriptive statistical analysis, classical assumption test, multiple regression analysis and then hypothesis testing. The independent variables in this study are corporate governance with proxies of the board of directors, independent commissioners, audit committee, and sustainability report. The dependent variable in this study is financial performance with ROE as a proxy. The results of the study show that corporate governance as proxied by the board of directors, independent commissioners, and the audit committee has no effect on financial performance, while the disclosure of sustainability reports has no effect on financial performance. Keywords: Corporate governance, board of directors, independent commissioner, audit committee, sustainability report, ROE